Assessing web surface credibility by generation Y: A Q methodological study - Mokrý, Stanislav (Mendelova univerzita v Brně, 2019)
Online marketing includes a variety of activities. Website presentation is one of the most striking. For many business providers it is vital to have a web-site and therefore there are currently more than 1.8 billion websites on the Internet. This situation has an impact on people who access the sites in terms of problems of decision making and confidence in the credibility of the website. This article deals with so-called surface credibility and analyses research data using the Q-method. The research was conducted with 70 respondents from generation Y. 40 anonymized web pages were used as sorted variables. The web pages were divided into 8 categories: financial institutions, universities, educational institutions, travel, lifestyle, commodity search engines, e-shops, health. Four factors were extracted and described. According to our study, the design quality; previous experience and similarity; graphical elements, website layouts and institutional framework are main elements playing the key role when assessing web surface credibility by generation Y. The main contribution of this article lays in its methodological approach by using Q-method in the innovative context of analysing web sites.
Keywords: Marketing communication; Q methodology; Web credibility